A novel TGFBR2 mutation causes Loeys-Dietz syndrome in a Chinese infant: A case report - Xin Liu; Kaiqing Liu; Lifu Hu; Zixiao Liu; Xinhua Liu; Jiantao Wang (Heliyon)
Introduction: Loeys‐Dietz syndrome (LDS) is a rare autosomal dominant disorder with extensive connective tissue involvement. The diagnosis of this disease is mainly based on clinical features combined with the detection of pathogenic gene mutations, mainly mutations in the transforming growth factor-beta (TGF-β) signaling pathway. Methods: The molecular pathogenesis of a LDS syndrome proband and his family members was analyzed using whole exome sequencing and validated using Sanger sequencing. Molecular dynamics simulations and in vitro cell experiments further analyzed the structural changes and functional abnormalities of the variation. Results: This study describes the case of a 6-month-old infant diagnosed with LDS with typical craniofacial abnormalities, developmental delay, and a dilated aortic sinus (19 mm; Z-score 3.5). Genetic analysis showed the patient carried a novel de novo TGF-β receptor 2 (TGFBR2) mutation (NM_003242: c.1005_1007delGTA (p.Glu335_Tyr336delinsAsp)). Molecular dynamics simulation showed that the TGFBR2 c.1005_1007delGTA mutation changed the protein conformation, making the protein conformation more stable. The p.Glu335_Tyr336delinsAsp mutation significantly reduced TGF-β-induced gene transcription and phosphorylation of SMAD Family Member 2 (SMAD2) in vitro. Conclusions: Our comprehensive genetic analysis suggested that the p.Glu335_Tyr336delinsAsp variant of TGFBR2 caused aberrant TGF-β signaling and contributed to LDS in the patient.